Self-tuning output passive-filter for low power DC/AC inverters - Arman, M. F.; Darwish, Mohamed K.; Marouchos, Christos (My University, 2012)
This paper presents a new type of output passive filters dedicated for voltage source inverters. The proposed filter is based on shunt single tuned filter topology which is modified by inserting a switched capacitor circuit. This filter can track unwanted harmonic components in the harmonic spectrum which might be a result of a variation in the inverter's output frequency. The proposed filter reduces harmonic components close to traditional single tuned filters performance. Mathematical analyses in conjunction with simulation results are shown to verify the design. Practical implementation of the overall system shows an excellent agreement with theory and simulation results.
Keywords: Mathematical analysis; Electromotive force; Filters and filtration; Switched capacitor circuits